Molecular characterization of vancomycin‐resistantEnterococcus faeciumstrains isolated from carriage and clinical samples in a tertiary hospital, Turkey. Issue 7 (July 2015) - Gozalan, Aysegul; Coskun‐Ari, Fatma Filiz; Ozdem, Birsen; Unaldi, Ozlem; Celikbilek, Nevreste; Kirca, Fisun; Aydogan, Sibel; Muderris, Tuba; Guven, Tumer; Acikgoz, Ziya Cibali; Durmaz, Riza
Abstract : N/A: This study aimed to determine the presence of vancomycin resistance ( vanA and vanB ) and virulence genes ( esp, asa1, gelE, ace, hyl, cylA, cpd and ebpA ) in vancomycin‐resistant Enterococcus faecium (VRE fm ) strains and to analyse the clonal relationships among the strains. E. faecium strains were identified from rectal and clinical specimens by biochemical tests and the API‐20 Strep kit. Susceptibility testing was performed using disc‐diffusion and broth‐dilution methods. PFGE was used for molecular typing of the VRE fm strains. The vancomycin resistance and virulence genes were amplified by two‐step multiplex PCR. All 55 VRE fm isolates were resistant to penicillin G, ampicillin and high‐level gentamicin but were susceptible to quinupristin/dalfopristin and linezolid. Multiplex PCR analysis indicated that all isolates harboured vanA and that 41 (75 %) were positive for virulence genes. The esp gene was the most common virulence factor and was detected in nine (41 %) invasive and 32 (96.7 %) non‐invasive isolates. Multiple virulence genes were observed only in two non‐invasive isolates; one harboured esp and ebpA and the other harboured esp, ebpA, asa1, gelE and cpd . PFGE typing yielded 16 different types, seven of which were clusters with two to 14 strains each. The clustering rates of the rectal swab, blood and urine isolates were 72.7 %, 61.5 % and 87.5 %, respectively. The genetic similarity observed among the VRE fm isolates indicated cross‐transmission in the hospital. Further studies on the virulence factors present in the strains might provide insight into the acquisition of these traits and their contribution to increased prevalence of VRE fm .